The Effectiveness of Manipulative Scales Media in Children’s Group B Measurement Concept Ability At TK Negeri Pembina Sragen - Indarwati, Ima; Diana, Diana (Indonesian Journal of Early Childhood Education Studies, 2017)
The using of manipulative scales is a learning media that is expected to increase the development of measurement concept ability accordance with the development level of children in group B. The use of manipulative scales media can be used effectively if teachers are creative in using supporting materials that can be found in surrounding environment to be used in developing measurement concept. The purpose of this research is to determine the effectiveness of using manipulative scales media toward measurement concept ability in measuring the length, volume, and weight for children’s Group B at TK Negeri Pembina Sragen. This research uses experimental methods with design One Group Pretest-Posttest Design. Sampling technique used in this research was purposive sampling with 43 children as sample. Hypothesis test obtain that based on statistical calculations which conducted, it obtained a t-test data through differences test Paired Sample t-Test on SPSS 18.0 program for windows t value is -38,083 with value sig(2-tailed) amounted to 0,000 < 0.05. This results show if the posttest result experienced an increase measurement concept ability that is higher than the pretest results. Viewed from the diagram picture 4.1 show an improvement achievement of mean value occurred in each measurement concepts that given, for the concept of length measurement from originally 34,67 into 43,88, for the concept of volume from 32,67 into 42,14, and the concept of weight from 33,42 into 42,02 and overall there is an increase mean value of measurement concept ability levels from group B from 100,77 into 128,05, resulting in increased score amounted to 27,28. The conclusion of this research is the use manipulative scales media can increase measurement concept ability in children’s group B, so that manipulative scales can be used by teacher as media in defining measuring concept of length, volume, and mass for student group B.